2019
DOI: 10.1038/s41598-018-37284-1
|View full text |Cite
|
Sign up to set email alerts
|

A gene expression signature in developing Purkinje cells predicts autism and intellectual disability co-morbidity status

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disease whose underpinning molecular mechanisms and neural substrates are subject to intense scrutiny. Interestingly, the cerebellum has emerged as one of the key brain regions affected in ASD. However, the genetic and molecular mechanisms that link the cerebellum to ASD, particularly during development, remain poorly understood. To gain insight into the genetic and molecular mechanisms that might link the cerebellum to ASD, we analysed the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Linking the findings of reduced cerebellar gray matter, the elaboration of the cerebellum in the perinatal period, and aberrant functional connectivity in ASD, recent transcriptomic profiling of Purkinje cells during development found that there is an enrichment of genes associated with ASD (Clifford et al, 2019). Interestingly, when compared to ASD-associated genes expressed during neocortical development, those in the Purkinje cell cluster were less likely to be associated with comorbid intellectual disability (Clifford et al, 2019). How this finding fits with other analyses linking high functioning, but not low functioning, ASD with cerebellar pathology warrants additional investigation (Noonan et al, 2009; Scott et al, 2009; Khan et al, 2015).…”
Section: The Cerebellum In Human Affective and Cognitive Diseasesmentioning
confidence: 99%
“…Linking the findings of reduced cerebellar gray matter, the elaboration of the cerebellum in the perinatal period, and aberrant functional connectivity in ASD, recent transcriptomic profiling of Purkinje cells during development found that there is an enrichment of genes associated with ASD (Clifford et al, 2019). Interestingly, when compared to ASD-associated genes expressed during neocortical development, those in the Purkinje cell cluster were less likely to be associated with comorbid intellectual disability (Clifford et al, 2019). How this finding fits with other analyses linking high functioning, but not low functioning, ASD with cerebellar pathology warrants additional investigation (Noonan et al, 2009; Scott et al, 2009; Khan et al, 2015).…”
Section: The Cerebellum In Human Affective and Cognitive Diseasesmentioning
confidence: 99%
“…Interestingly, although the cerebellum has classically been associated with motor function, there is increasing evidence for its role in cognition (Leiner et al, 1993; Vandervert, 2016) and as a key region in ASD susceptibility (Chen et al, 2017; Peter et al, 2016; Wang et al, 2014). This association has, however, been attributed to dysfunction of Purkinje cells (Box 1) (Clifford et al, 2019; Tsai et al, 2012), for which no correlate has been identified in Drosophila , thus limiting studies into this interesting topic.…”
Section: Using Drosophila To Overcome Bottlenecks In Id and Asd Reseamentioning
confidence: 99%
“…Interestingly, many of the monogenic, mendelian-inherited ASD genes have a high coexpression in the cerebellum. This growing list of genes includes, but is not limited to, SHANK2 and SHANK3, TSC1 and TSC2, and AUTS2 [4][5][6].…”
Section: Introductionmentioning
confidence: 99%